Effect of maternal or post‐weaning methyl donor supplementation on growth performance, carcass traits, and meat quality of pig offspring. (12th November 2018) - Zhao, Yang; Jin, Chao; Xuan, Yuedong; Zhou, Pan; Fang, Zhengfeng; Che, Lianqiang; Xu, Shengyu; Feng, Bin; Li, Jian; Jiang, Xuemei; Lin, Yan; Wu, De
Abstract: BACKGROUND: Limited studies have examined links between maternal methyl donor (MET) supplementation and the growth‐development characteristics of offspring, and possible underlying mechanisms for such links. This study investigated the effect of maternal or post‐weaning MET‐supplementation on growth performance, carcass characteristics, and meat quality of the finishing (d 180) offspring. Twenty‐four sows were placed on a control (C) or MET‐supplemented diet during pregnancy and lactation. Forty‐eight female offspring were fed the control or MET‐supplemented diet from weaning to 6 months of age, resulting in four study groups (six litters per group): C/C, C/MET, MET/C, and MET/MET. RESULTS: Maternal MET‐supplementation increased average daily gain (ADG), body weight (BW), lean percentage and longissimus dorsi (LD) of the offspring at day 180 ( P < 0.05), and upregulated the myosin heavy chain IIx, myogenic differentiation and muscle regulatory factor 4 mRNA levels in the LD muscle ( P < 0.05). Meanwhile, offspring from maternal MET‐supplementation exhibited a higher pH24h post mortem and superoxide dismutase activity, a lower L * 45min, glycolytic potential, malonaldehyde content in the LD muscle, and plasma homocysteine concentration ( P < 0.05). CONCLUSION: Maternal MET‐supplementation has a remarkable effect on growth performance, carcass traits, and meat quality of the offspring, which is associated with increased expression levels of myogenic genes and anti‐oxidant capacity. © 2018 Society of Chemical Industry